(untitled) - M. S. PALANICHAMY (New Delhi, 2000)
The book covers the civil engineering on 11 chapters: Civil engineering and materials, Foundation, Superstructure, Simple stresses and strains, Geometric properties of sections, Dams, Bridges, Surveying, Roads, Environmental engineering, Railways, Airports, Docks and harbours, Tall structures
Keywords: civil engineering